2015
DOI: 10.1142/s0218810415500239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Screw Design on Union Rates in Scaphoid Nonunions

Abstract: Our data revealed that the fully threaded conical screws were associated with significantly lower union rate compared to the smooth shaft Herbert type screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several biomechanical studies have shown that the fully threaded Acutrak screw produces higher compression forces than partially threaded smooth shaft HCSs (Assari et al, 2012; Gardner et al, 2012; Grewal et al, 2011; Hart et al, 2013). However, it has been suggested that too much compression force may affect fracture union (Wu et al, 2015). If indeed nonunion associated with Acutrak screws is associated with an increased compression force (Wu et al, 2015), it may then be acceptable to have an interfragmentary gap of 1–2 mm, such that the final compression force is within an acceptable range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several biomechanical studies have shown that the fully threaded Acutrak screw produces higher compression forces than partially threaded smooth shaft HCSs (Assari et al, 2012; Gardner et al, 2012; Grewal et al, 2011; Hart et al, 2013). However, it has been suggested that too much compression force may affect fracture union (Wu et al, 2015). If indeed nonunion associated with Acutrak screws is associated with an increased compression force (Wu et al, 2015), it may then be acceptable to have an interfragmentary gap of 1–2 mm, such that the final compression force is within an acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that too much compression force may affect fracture union (Wu et al, 2015). If indeed nonunion associated with Acutrak screws is associated with an increased compression force (Wu et al, 2015), it may then be acceptable to have an interfragmentary gap of 1–2 mm, such that the final compression force is within an acceptable range.…”
Section: Discussionmentioning
confidence: 99%